GALLURGIC CONCENTRATION OF TUPAKATON SYLVINITE ORE WITH AMMONIA (ResearchJet Journal of Analysis and Inventions, 2021)
The article outlines the use of potash fertilizer. Enrichments of sylvinite. Methods of enrichment. Complex cheese is used to enrich sylvinite. The solubility of 20-40oC of the three-component system KCl-NaCl-H2O has been studied.